Successful Optometric Vision Therapy with Patients on the Autistic Spectrum: Engaging Patients with Visual-Cognitive Therapy. - Azimi Green, Mehrnaz D.; Wachs, Harry; Dee, Mollie (Optometry & Visual Performance, 2014)
Approximately 1 in every 68 children is diagnosed with an autism spectrum disorder (ASD). It is one of the fastest growing disabilities in the United States, yet there is a shortage of optometrists who are able, and willing, to provide care for these patients. Visual-cognitive therapy (VCT) has been used for over 50 years to implement in-office vision therapy with challenging patients, including patients who have ASD. The following article presents the theory of VCT used with the DIR (Developmental, Individual differences, Relationship-based)/Floortime model to engage our patients with ASD. A brief discussion of visual-cognitive therapy and the DIR/Floortime model is presented along with examples of visual-cognitive therapy procedures.